Pengembangan Sistem Klasifikasi Karakteristik Siswa Berbasis Website dengan menggunakan Algoritma C4.5 - Paramita, Cinantya; Rafrastara, Fauzi Adi; Kencana, Lisdi Inu (Jurnal Informatika: Jurnal Pengembangan IT, 2023)
Student characteristics are one of the attributes of knowing a student's thinking skills and academic abilities. In the process of teaching and learning, appropriate learning strategies must be applied to students. The Hippocrates-Galenus typology categorizes personality types into four different categories, namely sanguine, choleric, melancholic and phlegmatic. Classification of characteristics that use an approach to students based only on experience or intuition can produce inaccurate results and take a lot of time to process. A system with the ability to predict student characteristics is needed in order to be able to assess students more quickly. In this study, the C4.5 algorithm was implemented into a system that aims to carry out the process of classifying the characteristics of students. From the results of the tests carried out, the C4.5 algorithm obtains an accuracy of 90.08%. This shows it is able to classify student characteristics well by using the C4.5 algorithm